Emerging digital generations? Impacts of child digital use on mental and socioemotional well-being across two cohorts in Ireland, 2007 2018 - Gracia, Pablo (My University, 2021)
Despite the growing body of literature on how digital technologies impact child well-being, previous research has provided little evidence on recent digital trends. This paper examines the patterns and effects of digital use on child socioemotional well-being across two cohorts of children grown up ten years apart during the ‘digital age’: the 1998 cohort (interviewed in 2007/08) and the 2008 cohort (interviewed in 2017/18). Multivariate linear regression models were conducted for these two cohorts from the Growing Up in Ireland (GUI) study, a multi-cohort longitudinal study with rich comparable data on a large sample of 9-year olds (N = 13,203). Results show that (i) in 2017/18 children were more active in digital devices and social media, while in 2007/2008 children spent more time watching TV and adopted less diversified forms of media engagement; (ii) spending more than 3 daily hours on TV/digital activities was associated with significant declines in child socioemotional well-being, while such effects were stronger in 2017/18 than in 2007/08; (iii) media engagement (but not other forms of digital engagement) was associated with moderate declines in socioemotional well-being, both in 2007/08 and in 2017/18; (iv) while children’s media and digital engagement differed by the child gender and socioeconomic background, none of these variables moderated the effects of digital use on children’s socioemotional well-being, neither in 2007/08 nor in 2017/18. Overall, the study reveals persistence, but also some important changes, in recent trends on children’s digital use and its impact on socioemotional well-being in Ireland.
PUBLISHED
Keywords: Digital use; Media; Child socioemotional wellbeing; Cohort effects; Ireland; Digital Engagement; Identities in Transformation; GLOBALIZATION; Information technology in education; Emotional-behavioural Problems; Mental Health/Psychosocial disability; Children; Development; Health; Youth